2018
DOI: 10.3389/fneur.2018.00795
|View full text |Cite
|
Sign up to set email alerts
|

Motor Overflow and Spasticity in Chronic Stroke Share a Common Pathophysiological Process: Analysis of Within-Limb and Between-Limb EMG-EMG Coherence

Abstract: The phenomenon of exaggerated motor overflow is well documented in stroke survivors with spasticity. However, the mechanism underlying the abnormal motor overflow remains unclear. In this study, we aimed to investigate the possible mechanisms behind abnormal motor overflow and its possible relations with post-stroke spasticity. 11 stroke patients (63.6 ± 6.4 yrs; 4 women) and 11 healthy subjects (31.18 ± 6.18 yrs; 2 women) were recruited. All of them were asked to perform unilateral isometric elbow flexion at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 52 publications
4
41
1
Order By: Relevance
“…It is likely that the clinical scales, such as MAS, lacks the sensitivity to quantify the abnormal tone with common definitions of stretch-reflex mediated spasticity [ 43 ]. In this study, we used an established biomechanical assessment method to quantify and differentiate reflex and non-reflex components of spastic hypertonia [ 10 , 11 , 44 ]. The results demonstrated significant decrease in the reflex component of spasticity, while the non-reflex muscular component remained unchanged after BoNT injections.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is likely that the clinical scales, such as MAS, lacks the sensitivity to quantify the abnormal tone with common definitions of stretch-reflex mediated spasticity [ 43 ]. In this study, we used an established biomechanical assessment method to quantify and differentiate reflex and non-reflex components of spastic hypertonia [ 10 , 11 , 44 ]. The results demonstrated significant decrease in the reflex component of spasticity, while the non-reflex muscular component remained unchanged after BoNT injections.…”
Section: Discussionmentioning
confidence: 99%
“…Spasticity is attributed to unopposed descending excitatory input to spinal reflex circuits from brainstem, and is related to disordered motor control [ 49 ]. In a recent study, it was found that reflex torque was correlated with spontaneous activity of spastic muscles [ 11 ]. Therefore, reduction of reflex torque after BoNT injections could indicate suppression of spontaneous activity in spastic muscles, and thus less “noise” during voluntary contraction of weakened spasticity muscles after BoNT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that children and adolescents affected by CP exhibit more mirror movements in their less affected hand, when performing movements with their more affected hand [ 30 , 33 ]. Even though patients with stroke did not show increased EMG activation on the contralateral side, they did exhibit increased ipsilateral muscle activation [ 34 ]. In line with those results, Sukal et al [ 35 ] found increased ipsilateral joint coupling for patients with hemiplegic CP.…”
Section: Discussionmentioning
confidence: 99%
“…The potential association between acoustic startle responses and intermuscular coherence during voluntary tasks has never been fully explored, and current evidence is indirect. For example, spasticity in chronic stroke is thought to relate to overdriven reticulospinal drive to muscles (74,75), and both alpha-band intermuscular coherence (76,77) and responses to acoustic startle are increased in spastic muscles of stroke survivors (78,79). However, if PD amplifies reticulospinal output, startle responses should be increased in magnitude or consistency relative to controls, but they are not (80).…”
Section: Neural Origins Of Parkinsonian Kinetic Action Tremormentioning
confidence: 99%